A survey-based estimation of the Swiss franc forward term premium - Lucas Marc Fuhrer; Basil Guggenheim; Matthias Paul Jüttner (Swiss Journal of Economics and Statistics, 2019)
This paper sheds light on Swiss franc LIBOR futures, which are often used to derive interest rate expectations. We show that the differences between LIBOR futures and realized rates (excess returns) are, on average, positive over the last 25 years. Using interest rate surveys, we decompose excess returns into a (forward) term premium and forecast errors. The decomposition reveals that the bulk of excess returns arises from forecast errors, while the term premium is, on average, zero but time varying. We find that the term premium positively correlates with the business cycle, interest rate developments, and in absolute values increases with interest rate uncertainty.
Keywords: E43; E44; E52; 330; Term premium; LIBOR futures; Swiss franc